2017
DOI: 10.1371/journal.pone.0175065
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic findings in infants with presumed congenital Zika syndrome: Retrospective case series study

Abstract: ObjectiveTo report the echocardiographic evaluation of 103 infants with presumed congenital Zika syndrome.MethodsAn observational retrospective study was performed at Instituto de Medicina Integral Prof. Fernando Figueira (IMIP), Recife, Brazil. 103 infants with presumed congenital Zika syndrome. All infants had microcephaly and head computed tomography findings compatible with congenital Zika syndrome. Zika IgM antibody was detected in cerebrospinal fluid samples of 23 infants. In 80 infants, the test was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 15 publications
2
34
0
2
Order By: Relevance
“…In the present report from an endemic area in tropical Asia, there is no problem of cardiac arrhythmia among the infected cases. 3 Focusing on the present report by Villamil-Gómez et al, the ECG problem is reversible, which might imply that there might be a reversible cardiac abnormality due to Zika virus infection. The exact underlying pathophysiology of abnormal ECG changes in the reported cases is unknown and might not relate to the Zika viruseinduced cellular pathology, which is generally not reversible.…”
Section: Electrocardiographic Finding In Zika Virus Infectionsupporting
confidence: 46%
“…In the present report from an endemic area in tropical Asia, there is no problem of cardiac arrhythmia among the infected cases. 3 Focusing on the present report by Villamil-Gómez et al, the ECG problem is reversible, which might imply that there might be a reversible cardiac abnormality due to Zika virus infection. The exact underlying pathophysiology of abnormal ECG changes in the reported cases is unknown and might not relate to the Zika viruseinduced cellular pathology, which is generally not reversible.…”
Section: Electrocardiographic Finding In Zika Virus Infectionsupporting
confidence: 46%
“…In a cohort reported by Brasil et al [5], a case with congenital Zika syndrome and congenital heart disease was present but details on the degree or type of heart disease were not provided. A recent study has found an increased prevalence of congenital heart disease in the form of atrial or ventricular septal defect in infants with presumed congenital Zika syndrome [17]. Arboviruses other than Zika are known to cause myocarditis and pericarditis [18,19], and viral antigen detection has been confirmed in myocardium and endothelial cells, so it is plausible that ZIKV infection could also cause heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that 13% of 103 intrauterine cases with ZIKV infection had cardiac anomalies such as ostium secundum atrial septal defect (in 5 of 14 cases), small apical ventricular septal defect (in 8 cases), and large ventricular septal defect (in 1 case) [56].…”
Section: Congenital and Intrauterine Zika Virus Infectionmentioning
confidence: 99%